Mapping the Active Site Helix-to-Strand Conversion of CxxxxC Peroxiredoxin Q Enzymes () - Perkins, Arden (2012)
Peroxiredoxins (Prx) are a family of enzymes which reduce peroxides using a peroxidatic cysteine residue; among these, the PrxQ subfamily members are proposed to be the most ancestral-like yet are among the least characterized. In many PrxQ enzymes, a second “resolving” cysteine is located six residues downstream from the peroxidatic Cys, and these residues form a disulfide during the catalytic cycle. Here, we describe three hyperthermophilic PrxQ crystal structures originally solved by the RIKEN structural genomics group. We reprocessed the diffraction data and carried out further refinement to yield models with R(free) lowered by 2.3–7.2% and resolution extended by 0.2–0.3 Å, making one, at 1.4 Å, the best resolved peroxiredoxin to date. Comparisons of two matched thiol and disulfide forms reveal that the active site conformational change required for disulfide formation involves a transition of about 20 residues from a pair of α-helices to a β-hairpin and 3(10)-helix. Each conformation has about 10 residues with high disorder providing slack that enables the dramatic shift, and the two conformations are anchored to the protein core by distinct non-polar side chains that fill three hydrophobic pockets. Sequence conservation patterns confirm the importance of these and a few additional residues for function. From a broader perspective, this study raises the provocative question of how to make use of the valuable information in the protein data bank generated by structural genomics projects but not described in the literature, perhaps remaining unrecognized and certainly underutilized.